Populism: A health check for constitutional democracy?. Issue 3 (April 2019) - Doyle, Oran; Longo, Erik; Pin, Andrea
Abstract: "Populism" appears everywhere: a frequently proffered assessment—or perhaps diagnosis—of constitutional systems around the world. Both its supporters and opponents emphasise its newness. But its phisiognomy, causes, and impact on legal orders and institutions are a matter of deep controversy. In a few words, its contours and core components adapt to different constitutional settings. Populist forces back a variety of agendas, which often overlap in a more rhetorically than concrete way. The authors of this issue divide themselves among opponents to populism and moderately optimistic observers. In this respect, populism has probably become a catalyst both for its supporters and detractors. Populism identifies through ideas that rally increasing number of discontents. But also opponents identify as populists the perceived threats to liberal democracy as they understand them. Defining populism has not simply proven to be a Sysyphean task; it has also showed that it is all but easy to pin down what a liberal democracy is made of. Contemporary debates about the fate of democracy need to abandon metaphysics for a more realistic, down-to-earth approach that is sensitive of the specificities of each constitutional setting.